2019
DOI: 10.1088/1755-1315/290/1/012166
|View full text |Cite
|
Sign up to set email alerts
|

Statistics and Governance. Current Issues of Affordable Housing: The Case of Prague

Abstract: Housing has become an issue around the world, both in emerging and developed countries. The affordability of housing is decreasing globally; however, the governance system can be harnessed as a tool to help to turn the situation around, the benefit being that it is in the hands of the local or national administration. The analysis of state of the art data, together with qualitative research based on the knowledge and experiences of experts, have been used to examine the case of Prague. The aim is to prove a di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
1
0
Order By: Relevance
“…Only a few scientific studies can be identified which share an interest in understanding the barriers to affordable housing provision, but they are somewhat narrow, especially in terms of the knowledge which they offer. These studies rely on single case study analyses focusing on individual issues instead of providing a comprehensive examination of the challenges which the sector is facing [43,[73][74][75][76].…”
Section: The Value Chain For Affordable Housing Supplymentioning
confidence: 99%
“…Only a few scientific studies can be identified which share an interest in understanding the barriers to affordable housing provision, but they are somewhat narrow, especially in terms of the knowledge which they offer. These studies rely on single case study analyses focusing on individual issues instead of providing a comprehensive examination of the challenges which the sector is facing [43,[73][74][75][76].…”
Section: The Value Chain For Affordable Housing Supplymentioning
confidence: 99%
“…As a matter of fact, a significant number of people are having difficulty in obtaining affordable and adequate housing (Arku, 2020). Therefore, as it stands now, the issue of affordable housing has affected both developed and developing countries (Hudecek et al, 2019). For example, Phang (2018) postulates that, shortage of adequate and affordable housing for low-and middle-income families has risen to the top of the social and political plan across cities in China and India.…”
Section: Introductionmentioning
confidence: 99%